The Determinants of Intellectual Capital Disclosure with Firm Age as a Moderating Variable - Suryani, Ayu; Khafid, Muhammad (Accounting Analysis Journal, 2021)
This research aims to examine and describe the relationship between profitability, leverage, foreign ownership, and government ownership on intellectual capital disclosure moderated by firm age. The population in this study is financial companies listed on the Indonesian Stock Exchange in 2017-2018. The sample selection uses the purposive sampling technique, which produced 81 companies and 162 units of analysis. Data collection using documentation techniques. Descriptive statistical analysis and moderation regression analysis were used to analyze data. The results showed that leverage and foreign ownership have a significant positive effect on intellectual capital disclosure, while profitability and government ownership do not affect intellectual capital disclosure. The result of the absolute difference test showed that firm age is able to moderate the effect of profitability and government ownership on intellectual capital disclosure but is not able to moderate the effect of leverage and foreign ownership. The findings prove highly leveraged companies and high foreign ownership encourage companies to disclose intellectual capital. Firm age weakens the effect of profitability and government ownership on intellectual capital disclosure. Keywords: Intellectual Capital Disclosure; Profitability; Leverage; Foreign Ownership; Government Ownership; Firm Age